2024
DOI: 10.3390/ani14050715
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Isochlorogenic Acid on Ewes Rumen Fermentation, Microbial Diversity and Ewes Immunity of Different Physiological Stages

Shuyan Li,
Xiongxiong Li,
Yuzhu Sha
et al.

Abstract: The effects of isochlorogenic acid (ICGA) on ewes rumen environment, microbial diversity, and immunity at different physiological stages (estrus, pregnancy and lactation) were studied in this experiment. Twenty healthy female Hu lambs of 1.5 months with similar body weight (17.82 ± 0.98 kg) and body condition were selected and randomly divided into two groups: the control group (CON) and the ICGA group (ICGA). The lambs of CON were fed a basal diet, while the lambs of ICGA were supplemented with 0.1% ICGA base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(26 reference statements)
1
0
0
Order By: Relevance
“…Of these, Prevotella had the highest proportion, while Rikenellaceae_RC9_gut_group was most closely related to the other genera. This is in agreement with previous studies that found that the predominance in the rumen of sheep was all Prevotella [11,17,74]. The high abundance of Prevotella is associated with a healthy microbial community and serves as the core of carbohydrate and hydrogen metabolism.…”
Section: Effect Of Hybridization On the Composition And Function Of T...supporting
confidence: 93%
“…Of these, Prevotella had the highest proportion, while Rikenellaceae_RC9_gut_group was most closely related to the other genera. This is in agreement with previous studies that found that the predominance in the rumen of sheep was all Prevotella [11,17,74]. The high abundance of Prevotella is associated with a healthy microbial community and serves as the core of carbohydrate and hydrogen metabolism.…”
Section: Effect Of Hybridization On the Composition And Function Of T...supporting
confidence: 93%